Non-stoichiometric crystallization of glasses in the combeite-devitrite (Na2O.2CaO.3SiO22Na2O.3CaO.6SiO2) joint: initial and advanced stages - Macena, Guilherme da Silva (2025)
It is known that glass is a condensed state of matter, non-crystalline and out of equilibrium, characterized by the glass transition phenomenon rather than a specific material. The structure of glass tends to relax toward that of the supercooled liquid related to the temperature at which it is found and crystallization. This phenomenon is of great importance in the production of glasses and glass-ceramics, materials produced by the controlled crystallization of glasses. A crystalline phase of significant technological and commercial interest is combeite, Na2O·2CaO·3SiO2, which finds various applications, from window glass to bioglasses. This composition easily forms a glass, relatively, and exhibits a solid solution range. The crystals initially show a high sodium concentration during solidification, progressively decreasing with subsequent growth. Aiming to understand the effect of non- stoichiometry and solid solution formation on crystallization, this work focused on studying the kinetics of combeite crystal formation in glasses within the Na2O·2CaO·3SiO2-Na2O·3CaO·6SiO2 joint. The nucleation rates were measured during the initial stages of crystallization, where the interaction of crystal nuclei can be neglected, along with growth and the variation in the composition of the crystals and the residual glass as the crystallization process advances. Optical and electron microscopy were used for microstructure characterization, differential scanning calorimetry (DSC) for monitoring the crystalline fraction and obtaining characteristic temperatures (liquidus and glass transition temperature, Tg), and energy-dispersive X-ray spectroscopy (EDS) for determining the composition of the present phases. The results show that the deviation of the parent glass composition from the stoichiometry of the precipitated crystals leads to a reduction in the thermodynamic driving force for crystallization and an increase in the interfacial energy between the crystalline nucleus and the supercooled liquid, significantly decreasing the nucleation rate. Quantitative analysis of concentration profiles in the diffusion zone, marked by calcium accumulation due to its rejection by the growing crystal, revealed that the nucleation rate significantly decreases near the crystal-glass interface, driven by the increased work required for critical nucleus formation caused by the higher calcium concentration. This study contributes to understanding the complex crystallization mechanisms of non-stoichiometric glasses and the fundamental knowledge and practical applications of these materials.